2008
DOI: 10.1016/j.neulet.2007.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cannabinoids attenuate carcinoma-induced nociception in mice

Abstract: We investigated the cannabinoid receptor (CBr) agonists Win55,212-2 (non-selective) and AM1241 (CBr2 selective) and the peripheral receptor (CBr1) in carcinoma-induced pain using a mouse model. Tumors were induced in the hind paw of female mice by local injection of a human oral squamous cell carcinoma (SCC). Significant pain, as indicated by reduction in withdrawal thresholds in response to mechanical stimulation, began at four days after SCC inoculation and lasted to 18 days. Local administration of Win55,21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 43 publications
3
27
0
2
Order By: Relevance
“…In several studies, local administration of cannabinoids into inflamed tissue attenuated hyperalgesia and allodynia via peripheral CB 1 Rs, at doses that produced only minimal centrally mediated side effects [22,23]. Activation of peripheral CB 1 Rs could reduce mechanical activation of A-δ nociceptors from inflamed skin but not from non-inflamed skin [24] and attenuated hyperalgesia produced by thermal injury [25], nerve injury [26] and cancer [27,28]. Moreover, the crucial role of peripheral cannabinoid receptors in the antihyperalgesic actions of systemically administered cannabinoids was also demonstrated by experiments with conditional peripheral CB 1 R knockout mice.…”
Section: Cannabinoids For the Treatment Of Pain: Preclinical And Animmentioning
confidence: 99%
“…In several studies, local administration of cannabinoids into inflamed tissue attenuated hyperalgesia and allodynia via peripheral CB 1 Rs, at doses that produced only minimal centrally mediated side effects [22,23]. Activation of peripheral CB 1 Rs could reduce mechanical activation of A-δ nociceptors from inflamed skin but not from non-inflamed skin [24] and attenuated hyperalgesia produced by thermal injury [25], nerve injury [26] and cancer [27,28]. Moreover, the crucial role of peripheral cannabinoid receptors in the antihyperalgesic actions of systemically administered cannabinoids was also demonstrated by experiments with conditional peripheral CB 1 R knockout mice.…”
Section: Cannabinoids For the Treatment Of Pain: Preclinical And Animmentioning
confidence: 99%
“…Studies in models of cancer pain have revealed differing effects on the expression of cannabinoid receptors within the CNS, with some groups reporting an upregulation of CB1 receptor in the L5 DRG in mice injected with squamous cell carcinoma into the hindpaw [46], while others studying models of bone cancer report no change in expression [48,60]. Despite these differences, administration of cannabinoid agonists produces robust analgesia in all models of cancer pain via activation of both CB1 [46,50,60] and CB2 receptors [46][47][48][49][50]. Interestingly, antinociceptive effects of both intrathecal and systemic administration of the CB2 receptor selective agonist AM1241 were abolished by intrathecal administration of the CB2 receptor antagonist SR144528, indicating a spinal site of action [48], and the effects of systemic AM1241 were blocked by naloxone [48], indicating a role of endogenous opioids, which warrants further investigation.…”
Section: Cb1 Receptor Modulation Of Pain Processing In Models Of Chromentioning
confidence: 99%
“…Local administration of cannabinoids have also been shown to attenuate hyperalgesia produced by nerve injury (Fox et al 2001;, cutaneous heat injury (Johanek and Simone 2004), and cancer (Guerrero et al 2008;Potenzieri et al 2008) through activation of peripheral CB 1 receptors.…”
Section: Cannabinoid Attenuation Of Allodynia and Hyperalgesiamentioning
confidence: 99%